Community Structure and Carbon Content of Mangrove Forest In The Bagek Kembar, Sekotong West Lombok - Hidayat, X Zardht Alex; Santoso, Didik; Syukur, Abdul (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Mangroves are tropical plants found in saline environments and have a function in regulating CO2 and O2 in the atmosphere. The aim of this research is to assess the community structure and carbon content of mangrove species in natural locations and revegetation results in Bagek Kembar, Sekotong, West Lombok. The research method uses transect and quadrat methods. The first data analysis was descriptive and then used carbon content analysis from the International Panel on Climate Change. The results of the research found 10 species of mangroves in natural locations, namely Avicennia alba, Avicennia marina, Bruguiera gymnorrhiza, Ceriops decandra, Excoecaria agallocha, Rhizophora apiculata, Rhizophora mucronata, Rhizophora stylosa, Sonneratia alba, and Sonneratia caseolaris, and in the revegetated locations were Avicennia marina, Rhizophora apiculata, Rhizophora mucronata, and Rhizophora stylosa. Furthermore, the seedling category has the highest density in natural mangrove locations with a total of 37976,19 individuals/Ha and in revegetated locations of 22361,11 individuals/Ha. The mangrove species that dominates in natural locations is the Avicennia marina species and in the revegetation results is the Rhizophora stylosa species based on frequency, density and dominance values. The highest biomass value in natural mangroves was obtained from the Avicennia marina species at 52,870 tonnes/ha, while in revegetated mangroves it was obtained from the Rhizophora stylosa species at 29,747 tonnes/ha. Furthermore, the total carbon content in natural mangrove locations is 59,329 tonnes C/ha or equivalent to carbon absorption of 183,018 tonnes CO2/ha. Meanwhile, the total carbon content in revegetated mangrove locations is 21,877 tonnes C/ha or comparable to carbon absorption of 80,290 tonnes CO2/ha. The research conclusion shows that the species that dominates and has the highest carbon content in natural locations is the Avicennia marina species and in revegetated locations is the Rhizophora stylosa species.